2013
DOI: 10.1097/cin.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Distance Learning Module on Premedication Antisepsis for Nursing Professionals

Abstract: The aim of this descriptive study, carried out at a public university, was to design, develop, and validate a distance learning module on intramuscular premedication antisepsis. The content was introduced in the Modular Object-Oriented Dynamic Learning Environment, based on the Systematic Model for Web-Based Training projects. Ten nurses and information technologists at work consented to participate, in compliance with ethical guidelines, and answered a questionnaire to validate the Virtual Learning Environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…There was no specific time limit to fill the pre-and post-test questions. The scores were graded as poor (0-3), fair (4-7) and good (8)(9)(10).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no specific time limit to fill the pre-and post-test questions. The scores were graded as poor (0-3), fair (4-7) and good (8)(9)(10).…”
Section: Data Collectionmentioning
confidence: 99%
“…7 Research has found web-based training systems to be successful in imparting continuous distance education in the fields of cytopathology, public health, premedication, antisepsis and nutrition. [7][8][9] Evidence suggests that medical nurses have limited knowledge about oral health of pregnant women and misconceptions about oral health. 10 Nurses who had clinical requirements regarding oral health assessment during nursing education had greater oral health competencies.…”
Section: Introductionmentioning
confidence: 99%